Social motives in intergroup conflict: group identity and perceived target of threat - Weisel, Ori; Zultan, Ro'i (Elsevier, 2016)
We experimentally test the social motives behind individual participation in intergroup conflict by manipulating the perceived target of threat—groups or individuals—and the symmetry of conflict. We find that behavior in conflict depends on whether one is harmed by actions perpetrated by the out-group, but not on one’s own influence on the outcome of the out-group. The perceived target of threat dramatically alters decisions to participate in conflict. When people perceive their group to be under threat, they are mobilized to do what is good for the group and contribute to the conflict. On the other hand, if people perceive to be personally under threat, they are driven to do what is good for themselves and withhold their contribution. The first phenomenon is attributed to group identity, possibly combined with a concern for social welfare. The second phenomenon is attributed to a novel victim effect. Another social motive—reciprocity—is ruled out by the data.